Makna dan Implementasi Ajaran Di Zi Gui di Vihara Kesejahteraan Kosambi Baru Jakarta Barat - Masithoh, Nimas Ayu; Tanggok, Muhammad Ikhsan (Inklusiva: Jurnal Studi Agama-Agama, 2023)
This study focuses on the meaning and implementation of Di Zi Gui teachings at Vihara Kesejahteraan Kosambi Baru, West Jakarta. The research employs a descriptive qualitative approach with field research and sociological methods. Primary data were obtained through in-depth interviews with the vihara's administrators, while secondary data were sourced from related literature. Data collection techniques include observation and interviews. The research informants were the vihara administrators with profound knowledge of Di Zi Gui teachings and the vihara’s activities. The study found that teachings  Di Zi Gui as a filial piety, simplicity, moral responsibility and self-control proved relevant in enhancing individual morality and social harmony.